2014
DOI: 10.1007/s11356-014-3031-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, possible sources, and health risk assessment of SVOC pollution in small streams in Pearl River Delta, China

Abstract: The pollution levels of typical semivolatile organic compounds (SVOCs) consisting of 15 polycyclic aromatic hydrocarbons (PAHs), 20 organic chlorinated pesticides (OCPs), and 15 phthalate esters (PAEs) were investigated in small rivers running through the flourishing cities in Pearl River Delta region, China. The concentrations of ∑15PAHs were 2.0-48 ng/L and 29-1.2×10 3 ng/g in the water and sediment samples, respectively. The ∑20OCPs were 6.6-57 ng/L and 9.3-6.0×10 2 ng/g in the water and sediment samples, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 47 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…Heavy metals, nitrites and organic pollutants in contaminated water and soil could increase the potential risk of cancers (Montesano and Hall, 2001;Hansen et al, 2003;Galiani et al, 2005;Wild et al, 2006;He, 2013). It is reported that contaminated water and food could even increase the morbidity and mortality of cancers, especially digestive cancers (Baudouin et al, 2002;Boffetta, 2006;Beaumont et al, 2008;El-Tawil, 2010;Gallagher et al, 2010;Ebenstein, 2012;Gao et al, 2012;Sun et al, 2014;Zhang et al, 2014;Zhao et al, 2014).…”
Section: Pollution Related Health Risks In Food Production Basesmentioning
confidence: 99%
“…Heavy metals, nitrites and organic pollutants in contaminated water and soil could increase the potential risk of cancers (Montesano and Hall, 2001;Hansen et al, 2003;Galiani et al, 2005;Wild et al, 2006;He, 2013). It is reported that contaminated water and food could even increase the morbidity and mortality of cancers, especially digestive cancers (Baudouin et al, 2002;Boffetta, 2006;Beaumont et al, 2008;El-Tawil, 2010;Gallagher et al, 2010;Ebenstein, 2012;Gao et al, 2012;Sun et al, 2014;Zhang et al, 2014;Zhao et al, 2014).…”
Section: Pollution Related Health Risks In Food Production Basesmentioning
confidence: 99%
“…In Japan, the concentrations of DEHP in the sediments of Jinzu River and Oyabe River were 0.02 μg/g to 0.30 μg/g and 0.02 μg/g to 1.80 μg/g, respectively [42]. The similar PAEs concentrations were also found in some sediments in China, including of Kaohsiung Harbor (DEHP, 0.40 μg/g to 34.80 μg/g; DBP, ND to 1.31 μg/g; DMP and DEP, ND) [43], the Pearl River Delta (DEHP, 0.03 μg/g to 170.0 μg/g; DBP, 0.310 μg/g to 2.8 μg/g; DEP, 0.009 μg/g to 0.12 μg/g; DMP, 0.003 μg/g to 0.20 μg/g) [44], and urban lakes in Guangzhou (DEHP, 0.21 μg/g to 14.16 μg/g; DBP, 0.082 μg/g to 1.26 μg/g; DEP, 0.028 μg/g to 1.05 μg/g; DMP, 0.001 μg/g to 0.43 μg/g) [45]. In most of the cases, DBP and DEHP were observed as the major PAEs in soils, attributing to their high octanol/water partition coefficient (Kow), which represented the migration of hydrophobic organic matters (PAEs in this study) between soils and water [46].…”
Section: Paes Absorption In Soilsmentioning
confidence: 99%
“…Organic pollutants in rivers included Dichlorodiphenyltrichloroethane [ 25 , 26 ], OCPs [ 27 , 28 ], PCBs, Hexachlorocyclohexanes (HCHs) and PAHs [ 29 , 30 ]. These organic pollutants are classical examples of POPs, with worldwide concern owing to their persistence, bioaccumulative ability, and potential negative impacts on humans and animals [ 31 ]. We have previously reported the toxicological significance of organic pollution of the drinking water source and its safety assessment to human health [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%